The legal protection for woman against violence: problems and prospects / Fadzilah Hassan - Hassan, Fadzilah (Faculty of Law, 1986)
The aim of this project paper is to look at every topical issue which causes public concern ie. violence against women. Violence canes in many forms either mental or physical. Common physical violence are rape, incests, sexual assaults and battery. Mental violence are the mental torture that the women has to endure in the hands of men. The writer also attempts to look at reasons behind the increasing number "of violence against women. The way women are portrayed over the mass media is one of the chief courses leading to this violence. This factor is contributed by the attitude of security towards women. Society viewed a woman only as a wife, mother or servant of men. When a woman gets raped she is ridiculed and society usually puts the blame on her for being raped. Conservative society viewed sex as something shameful and should not be discussed in public. As a result girls of tender age are ignorant and do not know what acts and attention showered on them are right or wrong.